(untitled) (UNIZIK Journal of Marketing, 2026)
The main objective of this paper was to examine the relationship between code of ethic and corporate core values among food and beverage firms in South East of Nigeria. The research design was survey research design. The population of the study was all registered food and beverage firms in Nigeria with operational base as South Eastern Nigeria. Available records from Nigeria Directory of statistics show that there are ninety-five (95) registered food and beverage firms in South Eastern Nigeria. The study adopted the total population of the study as the sample size because it was relatively small. The source of data for this work was primary. Data was collected through self-administered copies of structured questionnaire. Data collected were analyzed using Pearson correlation analysis. Correlation analysis was selected in this study because the primary objective is to determine the nature and strength of the relationship between two measurable variables. The findings showed that codes of ethics have a positive significant relationship with company core value. Based on the finding it was recommended that Managers in food and beverage firms should focus on regular ethics training, effective communication of ethical standards, and consistent enforcement mechanisms because it can help embed core values into daily operations.